A Comparative Study On The Photocatalytic Degradation Of Organic Dye In The Presence Of Biochar Composites Using Various Oxidants - Law, Zhi Xuan (2020)
The conversion of carbon-rich biomass into valuable material is an environmentally-friendly way for its utilization. In this study, coconut shellderived biochar, graphitic carbon nitride (g-C3N4), g-C3N4/biochar, titanium dioxide (TiO2)/biochar, zinc oxide (ZnO)/biochar and ferric oxide (Fe2O3)/biochar were synthesized and characterized by using scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDX), X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA), surface area analysis using BranauerEmmett-Teller (BET) method, UV-Vis diffuse reflectance spectroscopy (DRS) and zeta potential analysis. The SEM images illustrated the porous structure of biochar, flakes-like structure of g-C3N4 and the immobilization of nanometersized metal oxides on the biochar. The XRD and FTIR results of composite materials showed characteristic peaks of g-C3N4 and other metal oxides, indicated that g-C3N4 and metal oxides were well-immobilized on the biochar. TGA results presented the improvement of thermal stability of g-C3N4/biochar as compared to pure g-C3N4. Surface area analysis results showed that biochar could increase the specific surface area and average pore volume of catalyst sample. The band gap energies of g-C3N4, g-C3N4/biochar, TiO2/biochar, ZnO/biochar and Fe2O3/biochar were found to be 2.7 eV, 2.47 eV, 3.17 eV, 3.02 eV and 2.11 eV, respectively. Furthermore, zeta potential analysis proved that catalyst presented positively charged surface under acidic conditions, which favour the adsorption and subsequent degradation of anionic dye. Among different biochar composites, g-C3N4/biochar was found to be the best photocatalyst in the degradation of Methyl Orange. Besides, it was found that peroxymonosulfate (PMS) oxidizing agent could oxidized Methyl Orange better as compared to hydrogen peroxide (H2O2) and persulfate (PS), owing to the huge amount of hydroxyl radical (•OH) and sulphate radical (SO4• - ) generated. The effect of parameters such as catalyst dosage (0, 0.25, 0.50, 0.75, 1.0 and 1.25 g/L), PMS oxidant dosage (0, 0.2, 0.4, 0.6, 0.8 and 1.0 mM) and solution pH (pH 1, 3, 5, 7, 9 and 11) on the photocatalytic degradation of Methyl Orange were investigated. The highest degradation efficiency (92.71 %) was achieved at catalyst dosage of 0.75 g/L, PMS oxidant dosage of 0.6 mM and solution pH vi 3, which were further validated by using response surface methodology (RSM). According to the results of RSM, degradation efficiency of 96.63 % could be obtained under the optimum parameter condition (catalyst dosage of 0.75 g/L, PMS oxidant dosage of 0.57 mM and solution pH 3.48). In addition, the photocatalytic degradation of Methyl Orange using g-C3N4/biochar was found to have follow pseudo first order kinetic model. The overall chemical oxygen demand (COD) removal efficiency under the optimum operating condition was found to be 67.2 %. In short, g-C3N4/biochar could be a promising material in wastewater treatment process due to its good photocatalytic activity